2020
DOI: 10.1111/bph.15012
|View full text |Cite
|
Sign up to set email alerts
|

Aurora kinase inhibitor tozasertib suppresses mast cell activation in vitro and in vivo

Abstract: Background and Purpose: Mast cells are important in allergic reactions. Here, we assessed the anti-allergic effects of the anti-cancer drug tozasertib specifically regarding regulatory effects on mast cell activation. Experimental Approach: Tozasertib effects on mast cell degranulation were determined by measuring β-hexosaminidase and histamine release and by assessing morphological changes in RBL-2H3 and mouse bone marrow-derived mast cells (BMMCs) stimulated with mouse anti-dinitrophenyl (DNP)-IgE/DNP-human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 70 publications
3
13
0
Order By: Relevance
“…Our results showing that T-5224 reduced FcεRI-mediated degranulation in MCs were similar to previously reported effects of palbociclib (cyclin-dependent kinase inhibitor) and tozasertib (Aurora kinase inhibitor) [ 22 , 52 ]. Mechanistically, T-5224 decreased IgE/Ag-induced expression of EGR1 and IL4 and also blocked MAPK activation in activated MCs.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results showing that T-5224 reduced FcεRI-mediated degranulation in MCs were similar to previously reported effects of palbociclib (cyclin-dependent kinase inhibitor) and tozasertib (Aurora kinase inhibitor) [ 22 , 52 ]. Mechanistically, T-5224 decreased IgE/Ag-induced expression of EGR1 and IL4 and also blocked MAPK activation in activated MCs.…”
Section: Discussionsupporting
confidence: 92%
“…Mechanistically, T-5224 decreased IgE/Ag-induced expression of EGR1 and IL4 and also blocked MAPK activation in activated MCs. A variety of established medicines, including omeprazole (proton pump inhibitor) [ 7 ], tozasertib [ 52 ], and berberine (adenosine monophosphate-activated protein kinase stimulator) [ 53 ] inhibit MC activation-associated MAPK signaling. Meanwhile, T-5224 did not affect maturation of precursor cells into MCs (Additional file 1 : Figure S5).…”
Section: Discussionmentioning
confidence: 99%
“…MK-0457 (VX-680) is a small-molecule aurora kinase (AK) inhibitor [142,143] with preclinical anticancer activity [144]. MK-0457 has been assessed in phase II clinical trials in patients with Philadelphia chromosome-positive acute lymphoblastic leukemia (Ph + ALL) with the T315I mutation or treatment-refractory chronic myelogenous leukemia (CML) [145].…”
Section: Saha and Tozasertib (Mk-0457)mentioning
confidence: 99%
“…The function of Aurora C kinase is not well established, but studies suggested it has similar function to Aurora B kinase ( Sasai et al, 2004 ; Yan et al, 2005 ). There are several Aurora kinase inhibitors that have progressed to clinical development, including tozasertib ( Zhang et al, 2020 ), barasertib ( Floc’h et al, 2019 ) and MK-5108 ( Amin et al, 2016 ). Previous studies showed that GSK-1070916 has a broad antitumor effect on cancer cell lines and in tumor xenograft models including lung, breast, colorectal, and leukemia ( Hardwicke et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%